# factor f(x)=x^3+2x^2-15x-36

6,234 results

mat117/algebra
factor each polynomial completely. to begin, state which method should be applied to the first step, given the guidelines of this section. Then continue the exercise and factor each polynomial completely. 2p - 6q + pq - 3q^2 Please help, I don't know how or where to begin. I ...

Algebra
I have a question I hope someone can explain it to me. We are working on Demonstrate that f actoring a polynomial. I was ask Why can you factor x² - 4 but you cannot factor x² + 4? How can you tell quickly which ones you can factor and which you cannot? I am not sure what to...

algebra 2
f(x) =x^4 - x^3 -4x^2 +4. find factor and graph. I only factor to this step: (x^3 - 4x-4)(x-1) = f(x) but i don't know how to continue this step to require factor more completely and graph it. Please help. this is algebra 2. Thank you.

1.Factor 3/4 out of 3/4z+6. 2.Factor 18x+6y using the GCF. 3.Factor −5 out of −10a−25.

1.Factor 3/4 out of 3/4z+6. 2.Factor 18x+6y using the GCF. 3.Factor −5 out of −10a−25

math
f(x)=5,g(x)=2-3x^2,h(x)=10+15x^2 solve by inspection

Algebra
Solve the equation 3/x^2+15x+56 = 2x/x-7 - x/x-8

Geometry
B is the midpoint of AC, if AB=3x+4 and AC = 15x-19, find x and bc

calculus
Integrate x^2+5x+1dx/(2x^3+15x^2+6x+23)^1/2

math
solve with substitution 5x - y=-1 15x=2y

math
maximise p=15x+10y

maths
maximise p=15x+10y

Math
Solve. 25x^4-15x^2+2=0

algebra
What is the LCM of 15x^6 and 75x^8?

algebra 2
x intercepts of f(x)15x^2-12x-48

Calculus
Find the derivative of y=15x^7+7^x+22

1. 7r – 7 = 2r + 18 r = –5 r = 5 r = 2.2 r = 1.2 2. 2x + 12 = 18 – x x = 3 x = 10 x = 6 x = 2 3. 8x – 3 = 15x + 18 x = –3 x = 3 x = 2.1 x = .9 4. 6y – 6 = 4y + 16 y = 2.2 y = –2.2 y = 11 y = 5 5. 3(x – 4) = 5(x + 2) x = 11 x = –11 x = 1 x = –1

math
Divide: 3x - 15/14y ÷ x^2 -15x + 50/7

algebra
0.15x+0.05(50000-x)=5000

algebra
how do you do the linear equation y + 9 =1/5x and 45 - 3y = 15x

MATH

College Algebra
10x^2(x-8)^1/3 + 15x(x-8)^4/3

algebra
find the quotient (-9x^2 + 3x^2- 15x) - (-3x)

math
15x^2-102x=3 _____________ 7

ITT Tech
Simplify -(-15x)-3x

Maths
How to sketch graph of f(x)=x^3-7x^2+15x-9

algebra
divide 15x^2 + 10x -5 by 5x

College Algebra
15x^2-23x-21 /3x-7

maths
factorize completely X^2 + 2X^2 - 15X / 2X^2 - 18

Math 221
24x^5-15x^4/3x^2

Algebra Help
8x – 3 = 15x + 18 x = –3 x = 3 x = 2.1 x = .9 Can you show how you did it please?

algebra 1
How many solutions are in this equation 5x+y=15. 3y=-15x +6

Calculus
Find the derivative of f(x)=(2x)^(1/2)ln(15x)

Maths
X squared-36 and 2x square -15x+18

Math
Solving inequalities |1-15x/5| < 3

Math
I have a question that I answered and I'm not sure that it is right. Here is my question: Use a calculator to help you write the prime factorization of 51,051. Here is my answer: If the sum of the digits of the number is divisible by 3, then 3 is a factor of the number. ...

Algebra 1
factor out the greatest common factor. 7x^4-49x^3+14x^2=7x^2 Is this correct

MATH
How can you factor x^4 +1? If you go to the imaginary plane, it factors to (x^2 + i)(x^2-i) I need to factor by difference of squares. How can I do this?

Calc
How do you factor -2x^2+60x-120. I got -2(x^2-30x+60) but I need to factor it further.

Math
List all of the possible rational zeros of f(x)= 3x^5 - 7x^3 + 2x - 15. p= factor of 15 q= factor of 3 1,3,5,15 1,3 answer is 1,3,5,15,1/3,1,5/3,5

How would you factor 3x^3-4x^2+4x-1? P.S. Factor theorem does not work here.

alg 2
Can someone tell me how to factor 2a^2b - 16ab + 32b Should I factor 2b out of it?

college algebra
Factor out the greatest common factor from each polynomial 9y^2 -18y + 8

algebra
If (2x + y) is one factor of 2ax - 2bx + ay - by, what is the other factor? a) a - b b) a - y c) a + b d) a + x the answer i picked was a

factoring help
2 factor 4x -32x+48 and 2 2 2 factor (x -1)(x -4)(x -9) please and thank u verrry much is that this is due tommorow!!

Math209
I am not understanding how to factor polynomials. Example: Factor 12y^6-40y^5+28y^4

algebra
Factor out the greatest common factor from the expression 36x^3-30x^2

algebra
factor out the greatest common factor from the expression. 18x^7-14x^2

math
factor out the greatest common factor -36m^2n^3-60mn^4+18m^4n^2

Algebra
factor out the greatest common factor -36m^2n^3-60mn^4+18m^4n^2

intermediate algebra
factor out the greatest common factor from the expression 6x^3yz^4-3x^2y^3z^4-18^4y^2z^3

math
factor out the greatest common factor -36m^2n^3-60mn^4+18m^4n^2

algebra,math
Factor the GCF and then factor the resulting binomial: 50x^3 - 128x

algebra
Factor out the greatest common factor in the expression? 11y^5-55y^2

intermediate algebra
Factor out the greatest common factor from the expression 7x^2+56x-21

Math
synthetic division and the factor theorm indicate that x-3 is a factor of x^3-x^2-x-15.... true or false?

algebra
please help because am missing something.thankyou factor completely given that x+2 is a factor. 2x^3 + 7x^2 - 3x - 18

Math
If one factor of 56x^4y^3-42x^2y^6 is 14x^2y3,what is the other factor

Math
Factor 5x^2 -6x-4 I must be having an off day or something; this can factor, right!?

Factor. 1. 30y^3 - 50y A: 10y(3y - 5y) 2. Factor a^2 - 5a^2 + 2a -10 by grouping. A: ?

MATH FACTOR POLYNOMIALS
Factor the polynomial. Please show all work. x^2+2x-3

physics 2
to increse intensity o f a wave by a factor of 50, by what factor should the amplitude be increased?

Maths
31+x+31-x-10=0 Solve x2/3+x1/3-12=0 If (x-3)is a factor of x2+4x-21=0,find the other factor (using long division)

Calculus
How can you factor x^4 +1? I need to factor by difference of squares. How can I do this? change it to x^4 - (sqrt(-1))^2 or x^4 - i^2

mat117/algebra
Factor completely. ax - ay + x^2 - xy please show me how to factor this problem a(x-y) + x(x-y) = (a+x)(x-y)

math

college algebra
factor out the greatest factor from each polynomial 15R-27

algebra
factor: 9w - w^3 = 3w(3-w^2) m^4 - n^4 = (m-n)^2(m-n)^2 are these correct? the next few I wasn't sure how to work... factor: 2h^2 - h - 3 = 0 x^2 - 36 = 0 x^3 = 4x

Functions
use the factor theorem to determine whether x-c is a factor of f(x)=x^3+8x^2-18x+20; x-10.

Intermediate Algebra
factor out the greatest common factor from the expression. 35^8+35^5+28^3

Math
Factor out the common factor: −3x^4 y^2 + 18xy^3 + 9xy^4

math
If the area of a circle increases by a factor of 9, by what factor does its circumference increase ?

Mathematics
The product of two numbers is 3 1/4. One factor is 3 5/7. what is the other factor

Math
Factor and find all zeros. One factor is given. f(x)= 6x^3+7x^2-1; 2x+1

algebra
Factor out the greatest common factor from the expression 9a2b3 – 12a2b4 – 24a3b

algebra
factor out the greatest common factor from the expression 18x^5+48x^2-30x

Math
By what factor should each edge of a cube be increased in order to increase its volume by a factor of 27? a.) 27 b.) 9 c.) 3 d.) 2

college algebra
let f(x) be polynomial function. explain how to use the factor theorem to check if x) is a factor of F(x)

college algebra
x^3+4x^2-2x-3 ; x+1 factor theorum to decide whether or not second polynomial is a factor of the first.

math
Factor out the greatest common factor in each question. 1. 7× + 21 2. 12n - 9 3. 10c + 30 4. 10b + 25

Math
Factor and find all zeros. One factor has been given. f(x)= x^3+9x^2+23x+15; x+5

Math
I need help with these problems. I've gone over the material a lot, and I just don't understand! Please help fast, test is tomorrow! 1. Factor 4m²+40m+100 2. The area of a circle is given by the equation A = ð(25x²+10x+1). Find an expression for the radius. 3. The bed of a ...

physics
1. If the voltage impressed across a circuit is constant but the resistance increases by a factor of 15. By what factor does the current change? 2. If the resistance of a circuit remains constant while the voltage across the circuit decreases by a factor of 12, by what factor ...

homework statistics
Consider a random sample with sample mean x. If the sample size increased from n = 40 to n = 360, then the standard deviation of x will: a. remain the same b. increase by a factor of 9 (will be multiplied by 9) c. decrease by a factor of 9 (will be multiplied by 1/9) d. ...

Math
3x^3 -15x^2 -13x-4 what are the zeros of this problem?

algebra
Solve by elimination. 15x+10y=-20 3x+2y=-4

Math
7w 6wx === x === = 15x w Do I start by elimating the w?

help
7w/15x times 6wx/w How do I work this one

math
how do i go about solving this equation 3x=27-15x

Algebra

math
How do i expand and simplify (2x+5) (3x-4) 6x^2-8x+15x-20 6x^2+7x-20 Is this right??

math
find the x and y of the turning points of y=(x^3/3)-4x^2+15x-3

math
Solve the quadratic equation. 3x^2 - 15x + 18 = 0

Math
Simplify. 1.(-5x^2y)(3x^4) Is the answer for this = -15x^6y^1? If not could you explain how to do it? Thanks.

algrebra 2
how to find the xintercept and y intercept 5y=15x-90

Math
How would you solve this equation for x? y= -4x^3+15x^2-1

Math
How would you solve this equation for x? y= -4x^3+15x^2-1

math
7 + x < 20 15x > 50 7 + 14x > 35 need help in solving

algebra
0.15x+55>0.10x+80 how do i work this out?

Geometry
Z is between I and P. Solve for x and find IP. IZ= 3x+5 ZP= 4x+13 IP= 15x-22

Post a New Question